Preexisting phenols and resistance to aphid in cowpea (Vigna unguiculata [L.] Walp.) - Lattanzio, V.; Linsalata, V.; Maruca, G.; Marullo, R.; Singh, B.B.; Singh, S.R.; Perrino, P. (1990)
Phenolic compounds were analysed in leaf samples from 9 lines known to be resistant or susceptible to aphids (mainly Aphis craccivora but also, to a lesser extent, A. fabae). Resistant lines TVu3000, IT84E and IT83S742 had higher flavonoid glycoside contents than the susceptible lines VITA7, TVu3236 and IT82E. In the other 3 lines there was no clear relationship, which was attributed to sampling errors. Some of the phenolic compounds identified were tested in feeding experiments with A. fabae. The compounds interfering most with progeny deposition were p-coumaric acid, ferulic acid and quercetin.